THE FORMATION OF THE SOCIAL GROUP OF ACTORS IN LATVIA - Strads, Gatis (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
Theatre is one of the oldest forms of art due to its close nature to the life of people. Deriving from the point of epistemology, ontology and didactics, theatre poses its eternality... The most important concepts for the solution of social problems in education are individualization and socialization, individual activity of a personality and the interrelationship in a group, that has always been facilitated by culture, especially theatre performance.By analysing Latvian actors as a separate social group it is possible to trace its development process. The personality of actors in society opens up as its psychological and artistic activity. In order to carry out the analysis of social category, there is a need to analyse actor’s social relations. The activity of actors forms in its social group the cognitive image, that is socially relevant and which affects spectators. Theatre is the environment in which the actor lives and implements his/her social activity. Our theatre in the countryside is one of the strongest cognitive enlighteners, developers, and facilitators.The aim of the article is to provide the analysis of documents that give the insight into theatre companies and the formation of actors as a separate social group. The article also deals with the problems of modern theatre companies, and the ways how theatre companies have been developed.Research methods. Theoretical research methods include monographies, the analysis of research articles, the investigation of archive materials related to actors as a social group.